What’s in an Experiment? Roman Fish Sauce: an Experiment in Archaeology - Sally Grainger (EXARC, 2012)
This journal recently reported on an attempt to make fish sauce according to the recipe in Gargilius Martialis in order to asses their taste (Comis and Re 2009). This experiment seemed to fail on many levels and in fact the authors are quite honest in their conclusions that a great deal of further research is needed on the nature of these sauces before we can begin to consider what they may have tasted like. By a strange coincidence, at the time when I read this article in the summer of 2009, I was engaged in the preliminary preparations for extensive experiments to manufacture fish sauces for my MA dissertation in Archaeology at Reading University. My background is one which is ideally suited to engage in this project: as a professional chef who took a degree in Ancient History and went on to become a food historian, I have published widely on Roman food, including a new edition and translation of Apicius (Grocock and Grainger 2006). In my previous research into Roman food, it was clear that it was not going to be possible to truly understand ancient cuisine without first trying to gain some comprehension of the nature of garum and liquamen, and that required first hand experiments.